The Impact of the Application of the SQ3R Method on Understanding Physics Concepts on Measurement Material and Improving Learning Outcomes of Class X-I Students of SMA Negeri 3 Pamekasan. - Rohmatul Aini; Lia Koryataini; Suprianto; Nurul Hidayati; Rihana (Journal of Physics Education and Science, 2024)
The aim of this research is to evaluate the improvement in student learning outcomes through the use of the SQ3R method in understanding physics material regarding measurements in class X-I SMA Negeri 3 Pamekasan. The category of this research is PTK (classroom action research) with a total of 36 students. Data was collected through a test containing 5 questions. Before implementing the SQ3R method, the average student score was 56.67 and the level of learning completion reached 22.22%, which means that around 28 students had not achieved optimal understanding of the physics material. After this method was implemented, the test results showed an increase in the average score to 75.28 with a learning completion level of 61.11%, which shows that 22 students have succeeded in understanding physics concepts. The average increase in student grades was 38.89%. In cycle II, the focus of the material is more directed at analyzing single and repeated measurements. The results in cycle II showed an average class score of 82.22, with a learning completion level reaching 86.11%. Even though there has been an increase, there are still 5 students (13.88%) who have not achieved learning completion. Apart from that, the application of the SQ3R method also has a positive influence on student activity in learning. In cycle I, the level of physical activity was recorded at 50.57%, mental activity at 35.67%, and emotional activity at 61.11%. Meanwhile, in cycle II, physical activity increased to 86.27%, mental activity 92.24%, and emotional activity 87%.